Quality and labeling information of Moringa oleifera products marketed for HIV-infected people in Zimbabwe - Tsitsi Grace Monera-Penduka; Zvinji Tella Jani; Charles Chiedza Maponga; Josephine Mudzengi; Gene D. Morse; Charles Fungai Brian Nhachi (AOSIS, 2016)
Labeling information and quality of marketed Moringa oleifera products were assessed. Personnel in 60 pharmacies and 11 herbal shops were interviewed about the sources, dosages, indications and counseling information of Moringa oleifera products. Content analysis of written information provided on Moringa oleifera products was also done. Three samples of Moringa from popular sources were acquired to determine heavy metal content and microbial contamination. The results were compared to specified limits in the European and Chinese pharmacopeia, World Health Organization guidelines and Bureau of Indian Standards. Moringa was available as capsules or powder in 73% of the premises. Moringa was recommended for seven different disease conditions. Four different dosage regimens were prescribed. The main references cited for the counseling information were unscientific literature (62%). The selected Moringa samples were contaminated with bacteria and fungi above the European Pharmacopeia specified limits. Escherichia coli and Salmonella species were present in all three samples. All three samples contained arsenic, nickel and cadmium above the permissible limits. Moringa oleifera with variable labeling information and poor microbial and heavy metal quality is widely available in Zimbabwe.